Sistem Pakar Pemilihan Serum Wajah Menggunakan Metode Certainty Factor (Studi Kasus Produk Avoskin) - Puspitasari, Novianti; Mulia, Amalia Budiana; Hamdani, Hamdani; Masa, Amin Padmo Azam (Puslitbang Sinergis Asa Professional, 2024)
More and more people are aware of the importance of caring for facial skin, resulting in skincare production proliferating. Various kinds of skincare products are on the market, including facial serum. Facial serum is superior because it contains higher levels of active substances than other skincare products. The content and composition of a facial serum varies greatly and has different functions because the skin types and problems experienced are different. This means that users cannot use facial serum carelessly. Through this research, an expert system was created by applying the Certainty Factor method to identify facial serums, especially Avoskin products, which are expected to help the public determine facial serums that suit the type and skin problems they are experiencing. This study used 21 data on facial skin symptoms with eight types of Avoskin Your Skin Bae serum products. Based on the test results using the system accuracy percentage method, an accuracy of 85% was obtained so that the expert system created could run well.